The perceptions of students at Indera Mahkota MARA Professional College of English Language Proficiency and its role in preparation for employment - Nor Yazi, Khamis (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
This study aims to find out the perceptions of the students at Indera Mahkota MARA Professional College towards the importance of English language proficiency and its role in preparation for employment. The objectives are to identify the students’ proficiencies in the aspects of listening, speaking, reading, writing, grammar and vocabulary, and the use of the skills during their studies, as well as in the work force. The study seeks to identify the correlation between the students’ perceptions and its influence on their overall academic performance (CGPA). A set of questionnaire adapted from a survey by Hamidah Yamat@Ahmad et. al. (2003) was distributed to two hundred and twenty-five students of Diploma in Accountancy (DIA) and HND (Business Information Technology) (HNDBIT). Three hypotheses on finding differences in perceptions between programmes, demographic areas and gender have been tested and the score signifies no correlation between the students’ perceptions and their overall academic performance. This study proposes some recommendations to the existing Ministry of Education’s (KPM) English syllabi and to MARA Higher Education Department.